A cultural adaptation of Tinto’s student integration theory in undergraduate students of a private university in Colombia - Bibiana Castro-Montoya; Paulina Vélez-Gómez; Angela Segura-Cardona; Brian F. French (Cogent Education)
Dropout in higher education is a phenomenon of interest in both developed and developing countries; therefore, it is highly relevant to validate models that seek to explain it. This study aimed to determine the risk of dropping out in the first year using Tinto’s integration model, which incorporates students’ entry characteristics and aspects of institutional commitment and academic and social integration (SI) in the university environment. A prospective cohort study was conducted with 563 students enrolled in the 2019-1 and 2019-2 cohorts. Entry variables (demographic, socioeconomic, family and psychosocial) were measured, as well as the constructs of institutional commitment, academic and SI at two points in time, and dropout in the first year. Confirmatory factor analysis (CFA), factorial invariance over time, and structural equation modeling (SEM) were performed for the analyses. Family and psychosocial variables best explained the initial commitment of students. The initial commitment had significant effects on academic and SI, as well as on the subsequent commitment of the student, which, in turn, had a significant effect on the decrease in dropout rates. In conclusion, Tinto’s model was supported for explaining the dropout rate in Colombian university students, suggesting that beyond the student’s entry attributes, the interactions the student has with the academic and social system are critical to retention.